Analisis Perilaku Konsumen dalam Pengambilan Keputusan Pembelian Produk Eiger di Toko Eiger Kota Gunungsitoli - Hendriwan Novan Berkat Lase; Yupiter Mendrofa; Aferiaman Telaumbanua; Nanny Artatina Bu’ulolo (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the phenomenon of diverse consumer behavior in making purchase decisions for Eiger products at the Eiger Store in Gunungsitoli City, particularly amid the rapid growth of online stores and price competition from general stores such as Mr. DIY. This study aims to identify the factors influencing consumer behavior and to understand the process of purchase decision-making for Eiger products. The method employed is descriptive qualitative, with data collection techniques comprising in-depth interviews, observation, and documentation. The findings indicate that consumer behavior is influenced by internal factors, such as personal motivation and an active lifestyle in outdoor activities, as well as external factors including a strong brand image, high product quality, social recommendations from family and friends, and friendly and informative store service. The results of this study are expected to provide valuable input for store management in formulating more effective marketing strategies to enhance competitiveness in the local market